Vibrational and gravimetric analysis of polyaniline/polysaccharide composite materials - Gautam V.; Srivastava A.; Singh K.P.; Yadav V.L. (My University, 2025)
In this paper, we present a comparative study of polyaniline/polysaccharide composites (starch, carboxymethyl cellulose, cellulose acetate, and chitosan) by FTIR, UV-visible, SEM and electrochemical analysis. We propose that simultaneously three different phenomena happen while formation of composite system that may be listed as degradation of polysaccharide, polymerization of aniline, formation of polyaniline- polysaccharide composite. Effects of hydrochloric acid and oxidizing agent (ammonium peroxydisulphate) on the structure of polysaccharides were also investigated. We obtained dissimilar product yield and variable polyaniline and polysaccharide ratio in the composite system even though experimental conditions were same. The possible reasons responsible for the observed differences as well as characteristics and morphology of protonated and deprotonated composite materials are discussed. © 2016, Pleiades Publishing, Ltd.